Association of hearing impairment with insulin resistance, β–cell dysfunction and impaired fasting glucose before onset of diabetes. Issue 9 (6th March 2016) - Seo, M.; Lee, Y.‐S.; Moon, S.‐S.
Abstract: Aim: Diabetes is a known risk factor for hearing impairment. No study regarding the association of insulin resistance (IR), β–cell dysfunction and impaired fasting glucose (IFG) with hearing impairment has been reported in the population without diabetes. We examined these associations using a representative sample of the Korean population. Methods: Participants included 1589 males and 2496 females, who were ≥ 20 years of age and without diabetes from the Korea National Health and Nutritional Examination Surveys of the Korean population (2010). Audiometric tests and laboratory examinations were performed. Homeostasis model assessments of IR and β–cell function (HOMA–IR and HOMA–β) were calculated. Results: The prevalence of both high‐ and low‐/mid‐frequency hearing impairment among subjects with IFG was higher compared with those with normal glycaemia (42.2% vs. 24.5%, 14.7% vs. 7.8%, respectively). After adjustment for age, HOMA–IR and HOMA–β showed significant association with high‐frequency hearing impairment in males. In the multiple logistic regression analyses adjusting for confounding variables, the presence of IFG, higher HOMA–IR and lower HOMA–β remained as independent risk factors for high‐frequency mild hearing impairment in males < 70 years [odds ratio (OR) 1.441, 95% confidence interval (95% CI), 1.056 to 1.967; OR, 1.448, 95% CI, 1.039 to 2.101; and OR, 0.447, 95% CI, 0.274 to 0.729, P < 0.05, respectively). Conclusions: IR, β–cell dysfunction and IFG are associated with high‐frequency mild hearing impairment in the male population < 70 years before the onset of diabetes. What's new?: This is the first study to examine the association of insulin resistance, β–cell dysfunction and pre‐diabetes with hearing impairment in a population before the onset of diabetes, using a representative sample of the general population